Efektivitas Penggunaan Asam Asetat Pada Pemeraman Biji Kakao Segar Sebagai Analog Fermentasi - Pasau, Caturina (AGROTEKBIS, 2013)
This research is aimed to evaluate the effect of soaking the fresh cocoa beans without pulp (depulping has done before) in an acid solution and temperature controlled, analog fermentation. Fermentation of fresh cocoa beans without pulp in an Acetic acid solution will take place as a replacement for the two-stage fermentation with supporting temperature can accelerate the acidic compounds infiltrates into cocoa beans cotyledon for induced formation of taste and aroma precursor compounds. Research was conducted in the laboratory Nutrisi Dan Makanan Ternak, Faculty of Agriculture, Tadulako University. The acid solution to be used is Acetic acid pH 4.5 with incubation temperature 45oC (peak temperature in spontaneous fermentation) and dried cocoa beans accompanied by alkalization process and roasting. Roasted cocoa beans are tested by Sensory evaluation and were designed using a randomized block design within five processing of cocoa beans as treatments and sixteen untrained panellists as a group. The results showed temperature during analog fermentation, 44.32±0.72oC, is relatively as same as the peak temperature of spontaneous fermentation (45oC) and the final temperature of analog fermentation are higher than spontaneous fermentation, both of fermentation method ended by optimum fermentation temperature. At the end of fermentation pH values of analog fermentation, pH 5.4, is ​​higher than spontaneous fermentation, pH 4.41, that showed cocoa bean from spontaneous fermentation is more acidic than cocoa bean from analog fermentation. Changes in reducing sugar content during analog fermentation decreases more slowly than spontaneous fermentation and reducing sugar amount at the end of analog fermentation (13.88 mg/g) is larger than spontaneous fermented (8,86 mg/g) in fermented cocoa beans. Degradation protein content, based on its amount changing, during analog fermentation from 5.02% down to 4.86% is more than in spontaneous fermentation from 4.78% down to 4.70%, course of degrading protein content indicated a lot of free amino acids and peptides in fermented cocoa beans. However based on its amount, reducing sugar, free amino acids and peptides in fermented cocoa beans from analog fermentation is more adequate for further process of developing cocoa flavor. The best cocoa aroma was resulting from alkalized-roasted cocoa nibs of analog fermentation.